Current Treatment Options for Children with Functional Constipation—What Is in the Pipeline? - Charlotte A. L. Jonker; Tirza M. van Os; Ramon R. Gorter; Marc A. Levitt; Marc A. Benninga (Children)
In this review, we summarize current insights into the treatment of functional constipation (FC) in children. Constipation is a global issue in the pediatric population, with a prevalence of approximately 9.5%. Initial management involves a combination of non-pharmacological and pharmacological interventions. However, a significant number of children continue to experience therapy-resistant FC despite optimal non-pharmacological and pharmacological treatments. While studies on novel pharmacological options in children are limited, adult trials have shown promising results. New agents such as lubiprostone, prucalopride, linaclotide, and plecanatide have demonstrated improved outcomes compared to placebo or conventional therapies, particularly in increasing spontaneous bowel movements. Neurostimulation presents an additional treatment modality. Posterior tibial nerve stimulation appears to be a promising new option, offering high treatment satisfaction and a favorable safety profile with a low rate of severe adverse events. For children who do not respond to optimal conservative therapy, the impact on quality of life can be substantial. In such cases, surgical interventions may be considered, including intrasphincteric botulinum toxin injections, antegrade continence enema surgery, and, in severe cases, colonic resection or a diverting ostomy. The choice of surgical treatment remains a subject of ongoing debate. Therapy-resistant FC in children is a complex and impactful condition. An individualized, stepwise approach is essential, with surgical options such as colonic resection reserved as a last resort.